Medium formulation and optimisation of fermentation condition enhancing ɣ-aminobutyric acid (GABA) biosynthesis by Lactiplantibacillus plantarum B7 - Halim, Murni; Mohamad, Rosfarizan; Mohamed, Mohd Shamzi; Wasoh @ Mohamad Isa, Helmi; Faizal Wong, Fadzlie Wong (Journal of Pure and Applied Microbiology, 2024)
Extensive studies on γ-aminobutyric acid (GABA) over decades highlight its significant physiological and pharmacological effects on humans. GABA produce using microbe is favoured compared to enzymatic and chemical methods due to operational ease and reduced harmful pollutant formation. This study focused on increasing γ-aminobutyric acid (GABA) biosynthesis from Lactiplantibacillus plantarum B7, employing a multi-step optimisation strategy. An unoptimised fermentation approach yielded a maximum GABA of 11.675±0.04 g/L and viable cell count of 10.474 ± 0.01 log CFU/mL at 48 h. A nutrient-rich medium was developed through single-parameter optimisation, comprising 1%, 2.5% and 2 ppm of glucose, yeast extract and each trace element (CaCO3, KI, and Tween 80) respectively. Temperature, pH, incubation period, initial concentration of monosodium glutamate (MSG) and pyridoxal-5’-phosphate (PLP) demonstrated significant contributions towards GABA production and cell growth as determined using a two-level factorial design. Steepest ascent identified optimal conditions (36°C, pH 5.5, 370 mM MSG, and 0.7 mM PLP), resulting in 30.496 g/L GABA and 11.512 log CFU/mL at 60 h. Further refinement via a central composite experiment yielded optimal conditions (temperature-35.6°C, pH-5.66, initial MSG concentration-335.61 mM, PLP concentration-0.723 mM) with improved GABA production (32.182 g/L) and cell growth (11.524 log CFU/mL) over 63.66 h. Therefore, this approach utilising lactic acid bacteria capable of GABA synthesis holds promise for mass-produced, enhanced-functional foods.